High school reform and business reforms in education - Piolli, Evaldo (2022)
Work that analyzes the educational reforms triggered from 2016 in Brazil. It discusses the strategy of the business sector and its role in building consensus around its agenda, highlighting the Movement for the Base and how the BNCC theme gains centrality in the reform project. It analyzes the context of the enactment of the High School Reform, adopting the assumption that Law 13,415/2017 was a broad law of education reform in the country. By introducing the BNCC, the reform of secondary education triggered a broad reform of basic education, consolidating the business project focused on global tests, standardized assessments, accountability, as well as the flexibility of the curriculum, which occurred with the introduction of itineraries. training in high school. Curricular flexibility expands the possibilities of privatization of education with public-private partnerships and for distance learning. The reform reached higher education, especially with the enactment of the BNC – formation aligned with the BNCC matrices. Finally, it briefly presents some of the recent struggles and resistances of educators and social movements to this broad project of corporate education reform.